Assessing community structure and trophic interrelationships in three differently impacted headwater streams in the AmatholeWinterberg freshwater ecoregion, South Africa - Matomela, Nonjabulo Happy (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
Afromontane regions represent some of the highly threatened ecosystems on the planet as they harbour endemic and often relic freshwater fauna. These ecologically sensitive ecosystems have been altered by multiple impacts, including invasion by non-native fishes, replacement of diverse indigenous vegetation with monoculture plantations, agricultural and mining activities, hydrological modifications, and degradation of instream habitats, with potential detrimental effects on aquatic community structures and food web dynamics. The aim of the present study was to compare spatio-temporal patterns of macroinvertebrate and fish communities as well as food web dynamics in three differently impacted headwater tributaries of the Kat River in the Amathole-Winterberg freshwater ecoregion in the Eastern Cape Province of South Africa. The upper Kat River catchment was the ideal model for purposes of the present study as it contains streams with varying degrees of human impact. The streams considered in the present study were (i) the Eyre River which was considered to closely represent near-natural conditions as it is the least impacted stream in this catchment, with the riparian zone dominated by relatively intact and diverse native woody vegetation, (ii) the Elands River whose catchment has been altered by agricultural activities, and (iii) the Lushington River, whose riparian zone has been heavily invaded by black wattle. The three headwater streams were generally distinguished based on the physical-chemical variables. The Elands River was characterised by high conductivity and total dissolved solids (TDS). In addition, the Elands River was more alkaline and relatively warmer than the other two rivers. This suggested the negative influence of agriculture activities on the water quality in the Elands River. In general, the Lushington and Eyre rivers had comparable physical and chemical variables. However, the Lushington River was generally characterised by low streamflow, likely as a consequent of black wattle which is known for altering hydrological regimes of streams .The Eyre River and Lushington River were comparable in terms of macroinvertebrate richness and diversity, whereas the Elands River was characterised by low macroinvertebrate diversity and richness. Redundancy analysis indicated that the macroinvertebrate communities were mostly influenced by seasonality, with land-use accounting for a small but significant difference in community composition. In comparison, the generalised linear mixed-effects models (GLMMs) showed that chubbyhead barb abundance was significantly influenced by land-use patterns. Evaluation of food web dynamics using stable isotope analysis revealed that the food web structure in the three rivers differed substantially as a result of land-use. Specifically, the Eyre River was characterised by less variation in stable isotope values of basal food sources and consequently, the consumer groups had a narrow isotopic breadth. In contrast, the Elands River was characterised by a wide variation in basal food sources and therefore, a wider isotopic breadth for consumers. The Lushington River was spatially variable in terms of basal sources and isotopic breadth for consumers. The study concluded that food webs and trophic interrelationships were a more informative indicator of land-use than community structure was in evaluating the impact of land-use patterns on aquatic communities. In addition, future studies should seek to investigate food webs interrelationships in addition to community structure to infer a more conclusive river assessment.
Keywords: Stream ecology -- South Africa -- Eastern Cape; Freshwater animals -- Ecology -- South Africa -- Eastern Cape; Kat River (South Africa) --; Lushington River (South Africa); Elands River (South Africa); Eyre River (South Africa); Food chains (Ecology) -- South Africa -- Eastern Cape; Water quality -- South Africa -- Eastern Cape; Land use -- South Africa -- Eastern Cape